An analysis of cybersecurity culture in an organisation managing Critical Infrastructure - Parbhunath, Abraham (Department of Computer Science, 2022)
The 4th industrial revolution (4IR) is transforming the way businesses operate, making them more efficient and data-driven while also increasing the threat-landscape brought on by the convergence of technologies and increasingly so for organisations managing critical infrastructure. Environments that traditionally operated entirely independent of networks and the internet are now connecting in ways that are exposing critical infrastructure to a new level of cyber-risks that now need to be managed. Due to the stable nature of technologies and knowledge in traditional industrial environments, there is a misalignment of skills to emerging technology trends. Globally cyber-crime attacks are on the rise with Cisco reporting in 2018 that 31% of all respondents had seen a cyber-attack in their operational environment[1]. With up to 67% of breaches reported in the Willis Towers report due to employee negligence [2], the importance of cybersecurity culture is no longer in question in organisations managing critical infrastructure. Developing an understanding of the drivers for behaviours, attitudes and beliefs related to cybersecurity and aligning these to an organisations risk appetite and tolerance is crucial to managing cyber-risk. There is a very divergent understanding of cyber-risk in the engineering environment. This study endeavours to investigate employee perceptions, attitudes and values associated with cybersecurity and how these potentially affects their behaviour and ultimately the risk to the plant or organisation. Most traditional culture questionnaires focus on information security with observations focussing more on social engineering, email hygiene and physical controls. This cybersecurity culture study was conducted to gain insight into people's beliefs, attitudes and behaviours related to cybersecurity encompassing people, process and technology focussing on the operational technology environment in Eskom1. Both technical (Engineering and IT) and nontechnical (business support staff) staff were questionnaireed. The questionnaire was categorised into four sections dealing with cybersecurity culture as they relate to individuals, processes and technology, leadership and the organisation at large. The results from the analysis, revealed that collaboration, information sharing, reporting of vulnerabilities, high dependence and trust in technology, leadership commitment, vigilance, compliance, unclear processes and lack of understanding around cybersecurity all contribute to the current levels of cybersecurity culture. Insights from this study will generate recommendations that will form part of a cybersecurity culture transformation journey.